Health care pathways described by care-seekers following a call to the emergency medical communication center—A Swedish perspective - Jonas Wihlborg; Anna Carin Wahlberg; Mats Holmberg; Lars Sturesson; Annika Alm-Pfrunder; Veronica Lindström (PLoS ONE, 2025)
Introduction A call to an emergency number is often the first course of action among care-seekers seeking emergency care. The emergency medical communication centre assesses the call and dispatches resources to meet the care-seekers’ care needs. Knowledge concerning specific healthcare pathways is sparse and does not include the care-seeker perspective. Therefore, the aim of this study was to explore care-seekers’ experiences of healthcare pathways following a call to the national emergency number. Methods The study was an explorative cross-sectional study using data from telephone interviews with callers to the Swedish national emergency number. Study informants (n = 141) provided descriptions of incidents (n = 156) that led up to the call, as well as their experiences following a healthcare pathway. Data analysis included mapping healthcare pathways, descriptive statistics, and gathering descriptions of care-seeker experiences. Results and conclusions This study shows the multiple healthcare pathways for care-seekers following a call to the national emergency number. The accessibility and availability of the healthcare system are found to be difficult to grasp among care-seekers. Decisions on which pathway to follow are primarily made by healthcare professionals rather than the care-seekers, which supports the notion that the system is not being designed from the care-seekers’ perspective. Expressions of increased vulnerability, being unsafe and feeling lost were common among the care-seekers, regardless of which pathway was followed. The findings of this study could be used as an incentive for healthcare providers to develop a healthcare system based on the found novel knowledge of the care-seekers’ perspective.